The Effect of Asymmetry on Strain Distribution, Microstructure and Texture of Multilayer Aluminum Composites Formed by Roll-Bonding - Magalhães, D. C. C.; Rubert, J. B.; Cintho, O. M.; Sordi, V. L.; Kliauga, A. M. (Frontiers in Materials, 2020)
AA1050/AA7050 multilayered composite sheets with a proportion of 1:1 were produced by Accumulative Roll Bonding (ARB) and Asymmetric Accumulative Roll-Bonding (AARB), using up to 8 cycles and intermediate annealing treatments at 500 °C. The main purpose was to produce one composite sheet with high strength and moderate ductility, taking advantage of the mechanical properties of these aluminum alloys. Microstructural features were investigated in order to evaluate the potential to achieve a refined microstructure and the development of structural patterns. The strain distributions as a function of friction and asymmetry were simulated by finite element analysis. Texture was evaluated by X-ray diffraction and electron backscatter diffraction (EBSD). A continuous layer pattern was obtained by ARB, up to 6 cycles but after 8 cycles shear bands fragmented the harder layers. In the early AARB cycles, the bending and necking of the AA7050 layers yielded a wavy-pattern. The shear strain in the AARB process has a strong influence on achieving a wavy-pattern, more than the flow stress differences of the alloys in the composite. Shear texture increased with the degree of the layers’ discontinuity. Different sources of shear contributed to the formation of microstructural patterns: the shear due to asymmetry, the frictional shear at roll-sheet interface and at the central layer interface and the shear at the layers’ interface. In addition, the ARB process achieved a better interfacial adhesion at the middle interface and higher strength and elongation than the AARB process.